Hubungan Dukungan Keluarga dengan Self Esteem pada Pasien Kanker Payudara di Poliklinik Bedah Onkologi RSUP Sanglah Denpasar - Ni luh Putu Mahayani; Ni Komang Sukraandini; Ni Wayan Suniyadewi (Universitas Baiturrahim, 2020)
AbstractBreast cancer sufferers have a tendency to experience a decrease of self esteem that make patients shall showing symptoms such as blaming themself for what they experienced. One way to increase self esteem in cancer patients is by increasing family participation through family support. The aim of this study is to determine the relationship between family support and self esteem in breast cancer patients. This study was using cross sectional design. The study was taken place at the Surgical Oncology Polyclinic, found samples of 188 respondents which was selected with a purposive sampling technique.The results showed that the majority of respondents were in the category of moderate self-esteem were 98 respondents (52.1%) and the category of moderate family support were 96 respondents (51.1%). The Rank Spearmen test results shows p value 0,000 (p <ɑ), means there is a relationship between self-esteem and family support in breast cancer patients with r value of 0.566 (positive relationship). It is expected that the family will always support the patient in every process of treatment, whether in the form of physical, psychological or financial support that could increase the patient's self esteem